Analisis wacana kritis film the accountant: Special value akuntan forensik pengidap autistik - Rafles Ginting; David Crystopher; Khristina Yunita (Akuntansi dan Teknologi Informasi, 2024)
This study aims to reveal the relationship between autistic behavior and the basic characteristics that forensic accountants need to have. This research uses a critical discourse analysis method. Critical discourse analysis was carried out on the research object of the film "The Accountant". This study found that there are characteristics of autism that are in accordance with the basic characteristics that forensic accountants need to have. The basic characteristics that need to be possessed by forensic accountants which are also possessed by people with autism include being independent and objective. The nature of autism that makes a person have an indifferent attitude towards the environment can actually be used as a factor for the success of forensic accountants. This research opens up views on autistic people who also have potential in the field of forensic accounting. This study also invites readers not to underestimate people who have autism. The novelty in this study is the object of research that focuses on forensic accounting from the point of view of people with autistic disorders.